Dramaturgi Komunikasi Dakwah Para Da’i di Kota Ambon: Pola Pengelolaan Kesan di Panggung Depan - Sulaeman, Sulaeman; Sulastri, Irta; Nurdin, Ali (Jurnal Komunikasi Islam, 2018)
This article discusses the pattern of impression management carried out by the da’i on the front stage in an effort to improve the quality of message transformation to mad’u. Through a good impression management, the persuasion process occurs which allows the conveyed messages to be well received by mad’u with fullly awareness, not by force. Using dramaturgy approach, researchers conducted participatory observation and in-depth interviews towards 15 da’is in Ambon City who were chosen purposively. This study has revealed that during proselytizing, the da’is manage the impression on the front stage by utilizing verbal and nonverbal communication through the management of situational, planned, and spontaneous impressions.